Welcome to Westonci.ca, where your questions are met with accurate answers from a community of experts and enthusiasts. Experience the ease of finding accurate answers to your questions from a knowledgeable community of professionals. Join our Q&A platform to connect with experts dedicated to providing accurate answers to your questions in various fields.
Sagot :
Answer:
[tex]x=1[/tex]
[tex]y=2[/tex]
Step-by-step explanation:
[tex]y=x^2+3x-2[/tex] , [tex]y+3=5x[/tex]
Replace all occurrences of [tex]y[/tex] in [tex]y+3=5x[/tex] with [tex]x^2+3x-2.[/tex]
[tex](x^2+3x-2)+3=5x[/tex]
[tex]y=x^2+3x-2[/tex]
Add [tex]-2[/tex] and 3.
[tex]x^2+3x+1=5x[/tex]
[tex]y=x^2+3x-2[/tex]
Subtract 5x from both sides of the equation.
[tex]x^2+3x+1-5x=0[/tex]
[tex]y=x^2+3x-2[/tex]
Subtract 5x from 3x.
[tex]x^2-2x+1=0[/tex]
[tex]y=x^2+3x-2[/tex]
Rewrite 1 as [tex]1^2[/tex].
[tex]x^2-2x+1^2=0[/tex]
[tex]y=x^2+3x-2[/tex]
Check that the middle term is two times the product of the numbers being squared in the first term and third term.
[tex]2x=2[/tex] · [tex]x[/tex] · [tex]1[/tex]
[tex]y=x^2+3x-2[/tex]
Rewrite the polynomial.
[tex]x^2-2[/tex] · [tex]x[/tex] · [tex]1[/tex] [tex]+[/tex] [tex]1^2=0[/tex]
[tex]y=x^2+3x-2[/tex]
Factor using the perfect square
trinomial rule [tex]a^2-2ab+b^2=(a-b)^2,[/tex]
where a = x and b = 1.
[tex](x-1)^2=0[/tex]
[tex]y=x^2+3x-2[/tex]
Set the [tex]x-1[/tex] equal to 0.
[tex]x-1=0[/tex]
[tex]y=x^2+3x-2[/tex]
Add 1 to both sides of the equation.
[tex]x=1[/tex]
[tex]y=x^2+3x-2[/tex]
Replace all occurrences of [tex]x[/tex] in
[tex]y=x^2+3x-2[/tex] with 1.
[tex]y=(1)^2+3(1)-2[/tex]
[tex]x=1[/tex]
[tex]y=2[/tex]
We appreciate your time. Please revisit us for more reliable answers to any questions you may have. Your visit means a lot to us. Don't hesitate to return for more reliable answers to any questions you may have. Thank you for visiting Westonci.ca. Stay informed by coming back for more detailed answers.